Pharmacogenetics association with long-term clinical evolution in a kidney transplant patients cohort - Luis Sendra; Gladys G. Olivera-Pasquini; Enrique G. Zucchet; Fabiana D.V. Genvigir; María Isabel Beneyto; Julio Hernández-Jaras; María José Herrero; Salvador F. Aliño (Current Research in Pharmacology and Drug Discovery)
Background: Pharmacogenetic variability has been reported to influence the efficacy and safety of immunosuppressive therapies in early stages of kidney transplantation. This study investigates long-term associations between pharmacogene variants and clinical outcomes in a cohort of kidney transplant recipients over a 12-year follow-up. Materials and methods: We analyzed 37 SNPs from 14 genes related to drug metabolism and transport in 79 kidney transplant patients. Clinical parameters, including survival, renal function, tumor occurrence, and pharmacokinetics of tacrolimus, were evaluated. Logistic regression and Kaplan-Meier analyses assessed associations between gene variants and clinical outcomes. Results: Variants in metabolizer (CYP3A5, CYP2B6) and transporter genes (ABCB1, ABCC2) were associated with 12-year survival. Increased tumor risk correlated with ABCC2 variants in donors and decreased risk with CYP2B6 rs3745274 in recipients. Renal function was influenced by variants in ABCB1, ABCC2, CYP3A5, CYP3A4, and CYP2B6. Tacrolimus dose-dependent concentration was affected by variants in CYP3A4, CYP3A5, CYP2C19, ABCB1, and SLCO1B1. Increased nephrotoxicity risk was associated with CYP2C19 rs4244285 and reduced by SLCO1B1 rs2306283 AA and AG variants. Gene variant interactions between metabolizer and transporter genes were also associated with altered risk of events incidence. Discussion: Our findings support that pharmacogene variants influence transplant outcomes. Notable associations include survival related to ABCB1 and ABCC2 variants, tumor occurrence linked to CYP2B6 rs3745274, and renal function affected by multiple pharmacogenes. Variants in CYP2C19 and SLCO1B1 significantly impacted tacrolimus pharmacokinetics and nephrotoxicity risk. These results underline the importance of pharmacogenetic testing for personalized management in kidney transplantation, although further validation in larger cohorts is necessary.